Heritability of intraocular pressure: a classical twin study. Issue 8 (24th July 2008) - Carbonaro, F; Andrew, T; Mackey, D A; Spector, T D; Hammond, C J
Abstract : Aims: To estimate the heritability of intraocular pressure (IOP) by performing a classical twin study and to determine whether the use of different instruments influences calculation of eye IOP heritability. Methods: Twin pairs were recruited to participate from the TwinsUK Adult Twin Registry at St. Thomas' Hospital London. IOP was measured using Goldmann applanation tonometry (GAT). A subset of twins also had their IOP measured using the Ocular Response Analyser (ORA; Reichert, Buffalo, NY) and the Dynamic Contour Tonometer (DCT, Pascal; Swiss Microtechnology AG, Port, Switzerland). We compared the covariance of IOP within monozygotic (MZ) and dizygotic (DZ) pairs using genetic modelling techniques to determine the relative contribution of genes and environment to the variation in IOP seen in this population. Results: Data for 422 twin pairs (211 MZ; 211 DZ) were analysed. The mean IOP for GAT was 15.4 (SD 2.7) mm Hg (range: 8.7–26.2 mm Hg). The MZ correlations were significantly higher than DZ for IOP measured by GAT, DCT and ORA (correlation coefficients: GAT: 0.57:0.39, DCT: 0.62:0.36, Goldmann-correlated ORA (IOPg) 0.73:0.47, for MZ:DZ twins, respectively). Modelling suggested heritability for GAT IOP of 0.62, with individual environmental factors accounting for 0.38 of the variation. Conclusion: This study demonstrated that genetic effects are important in determining IOP in this twin population. IOP readings differed depending upon the instrument used, and this resulted in different heritability values; genetic factors explained 62%, 63% and 74% of the variation in IOP using GAT, DCT and ORA IOPg, respectively. Environmental factors determined the remainder of the variation.